Potential use of medicinal plants from Argentinean highland as agent anti‐photoaging. (11th October 2020) - Orqueda, María Eugenia; Moreno, María Alejandra; Zampini, Iris Catiana; Bravo, Karent; Osorio, Edison; Isla, María Inés
Abstract: Background: The overexposure to sun ultraviolet (UV) radiation produce photoaging by effect of free radicals on lipid, protein, and nucleic acid or by direct activation of responsible enzymes of cleavage of extracellular matrix components (EMC). Aims: To develop new anti‐photoaging agents, the anti‐aging activity of four "jarillas" standardized extracts from Argentina ( Zuccagnia punctata Cav., Larrea divaricata Cav., Larrea cuneifolia Cav., and Larrea nitida Cav.) were examined. Methods: The effect on the activity and expression of enzymes related to photoaging (collagenase, hyaluronidase, elastase, tyrosinase) and the antioxidant capacity of four "jarillas" extracts were examined. Results: The results suggest that "jarillas" extracts could protect EMC by inhibition of skin aging‐related enzymes and suppression of the expression of metalloproteinases (MMP‐1) in human skin fibroblasts from photoinduced damage. Modulation of MMP‐1 expression induced by UV radiation in human skin cells could be associated, at least in part, with the ROS scavenging capacity of "jarilla" extracts. The extract of Z punctata was more active than Larrea species extracts in all the trials. The activity of Z punctata and Larrea extracts could be ascribed to chalcones and lignans, major constituents of "jarillas, " respectively. Conclusions: The results obtained would indicate the potential of these adapted species to live in arid zones of Argentina, exposed to high ultraviolet radiation in production of cosmetic products and justify the promotion of their sustainable use and the development of crops.